The effect of protease inhibitor‐based dual antiretroviral regimens on CD4/CD8 ratio during the first year of therapy in ART‐naïve patients with HIV‐infection. Issue 4 (17th December 2020) - Figueroa, MI; Camiro‐Zuñiga, A; Belaunzaran‐Zamudio, PF; Sierra Madero, J; Andrade Villanueva, J; Arribas, JR; Lama, JR; Cecchini, DM; Lopardo, G; Crabtree‐Ramírez, B; Gun, A; Patterson, P; et al.
Abstract : Objectives: To assess the effect of protease inhibitor (PI)‐based dual therapy on CD4/CD8 ratio during the first year of therapy in antiretroviral therapy (ART)‐naïve patients using data from randomized controlled clinical trials. Methods: We pooled data from the GARDEL and ANDES studies, both randomized controlled clinical trials that recruited ART‐naïve people living with HIV and randomly assigned them to receive PI‐based dual therapy (DT) or triple therapy (TT) aiming to compare viral efficacy. We compared median CD4/CD8 ratios and the proportion of patients with CD4/CD8 ratio > 1 at 48 weeks after ART initiation in both treatment arms using the Mann–Whitney U ‐test and the χ 2 test. We performed subgroup analysis for patients > 50 years old, with baseline CD4 counts ≤ 200 cells/μL, viral load > 100 000 HIV RNA copies/mL, and ritonavir‐boosted lopinavir‐based therapy. Results: We analysed data from 571 patients: 292 on DT and 279 on TT. No differences were observed in CD4/CD8 ratio (0.632 vs . 0.617, P  = 0.729) or in the proportion of patients with CD4/CD8 ratio > 1 (17.9% vs . 19.3%, P  = 0.678) 48 weeks after ART initiation. Subgroup analysis showed no further differences. Conclusion: The impact of PI‐based DT regimens on the CD4/CD8 ratio during the first year of treatment for ART‐naïve patients is similar to that of TT.